IMPLEMENTASI PENGELOLAAN ALOKASI DANA DESA (ADD) DI KAMPUNG LINGGANG MAPAN KECAMATAN LINGGANG BIGUNG KABUPATEN KUTAI BARAT - Nova Sintia Dewi Sitorus; Anthonius Margono; Bambang Irawan (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this study is to describe and analyze the Village Fund Allocation Management Implementation (ADD) In Kampung Linggang Mapan District of Linggang Bigung West Kutai, as well as to describe and analyze the factors influencing the effectiveness of it. The study concluded that the ADD Policy Implementation in the village Linggang Mapan not run optimally. It can be seen from the lack of understanding ADD management team in planning the implementation of ADD fund management activities, because the planning process is only done by the team manager of ADD without involving all villagers.